Digital transformation and its multidimensional impact on sustainable business performance: evidence from a meta-analytic review - Dedrix Stephenson Bindeeba; Eddy Kurobuza Tukamushaba; Rennie Bakashaba (Future Business Journal)
Abstract Digital transformation has become a strategic driver of sustainable business performance, offering new pathways for firms to achieve economic, environmental, and social goals. This study conducts a meta-analysis to synthesize empirical evidence on the relationship between digital transformation and sustainable business performance. A total of 153 effect sizes from 44 empirical studies, comprising 17,284 observations, were analyzed using Comprehensive Meta-Analysis software and a random-effects model. The findings reveal a significant positive relationship, with the strongest impact observed on economic performance, followed by environmental and social performance. Among the technologies examined, smart factories, big data analytics, and the Internet of Things emerged as the most influential enablers of sustainability outcomes. Subgroup analyses showed higher impacts in lower-middle-income countries and specific sectors such as telecommunications and manufacturing. Methodologically, studies using structural equation modeling reported stronger effect sizes than those using regression analyses. These results demonstrate the multidimensional benefits of digital transformation, particularly in improving productivity, reducing environmental impact, and fostering stakeholder engagement. The study contributes a comprehensive evidence base for guiding digital adoption strategies and policymaking in support of sustainable development.